Living Lab Implementation in Civic Education to Internalize National Spirit and Responsibility Character - Nurdiansyah, Edwin; Sapriya, Sapriya; Darmawan, Cecep; Aim Abdulkarim; Kurniawan, Dedi (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2025)
Civic Education learning still tends to be textual and less contextual, making it less interesting and ineffective in building students' character. This study explores the effectiveness of implementing the living lab learning model in shaping the character of national spirit and responsibility of students. This study used a quasi-experimental design with pre-test, post-test assesments and questionnaires which involved 232 Sriwijaya University students as research respondents. Analyzed using the N-Gain value and Pearson correlation. The results from implementation of the living lab indicated a moderate improvement in students' character, particularly in collaboration, social involvement, and sensitivity to national issues. Based on statistical analysis, a significant correlation was obtained between the implementation of this learning model and the development of students' character (p-value <0.05). This shows that the living lab approach allows learning to be more contextual and collaborative, as well as provides real experiences that are relevant to build students' character in facing the challenges of the 21st century. Longitudinal studies to evaluate the sustainability of the impact of this model in a long-term context are recommended for future research.